Role of preservation methods using deep-freezing and liquid nitrogen in bone allograft characteristics: An in vitro study - Lisan, Rizal A.; Mahyudin, Ferdiansyah; Edward, Mouli; Buwana, Dewan S. (Narra J, 2024)
Bone grafting has emerged as a key solution in bone defect management such as allograft, graft of bone from another individual. However, bone allografts usually undergo rigorous preparation to eliminate immune-triggering elements. The deep-freezing methods may delay graft use, while cryopreservation using liquid nitrogen allows rapid freezing but may alter graft characteristics. The aim of this study was to investigate the post-preservation changes in bone allograft characteristics and to compare the effectiveness of deep-freezing and liquid nitrogen methods using animal model. An experimental study using a post-test only control group design was conducted. Fresh-frozen femoral cortical bone was obtained from male New Zealand white rabbits. Preservation by deep-freezing involved placing bone samples in a -80°C freezer for 30 days. For liquid nitrogen preservation, bone grafts were immersed in liquid nitrogen for 20 min, followed by a 15-min rest at room temperature and a final immersion in 0.9% sodium chloride at 30°C for 15 min. Bone samples then underwent evaluation of cell viability, compression, and bending tests. Cell viability test employed the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay and the compression and bending tests used the Universal Testing Machine (UTM). Independent Student t-test or Mann-Whitney U test were used to compare the methods as appropriate. Our study found that the use of deep-freezing and liquid nitrogen resulted in similar outcomes for cell viability, compression, and bending tests, with p-values of 0.302, 0.745, and 0.512, respectively. Further exploration with larger sample sizes may help to optimize the methods for specific applications.